RETRACTED: Akt Inhibition Enhanced the Growth Inhibition Effects of Low-Dose Heavy-Ion Radiation via the PI3K/Akt/p53 Signaling Pathway in C6 Glioblastoma Cells - Huang, Ke; Zhao, Wei; Wang, Xuqiao; Qiu, Yingfei; Liu, Zelin; Chen, Rui; Liu, Wei; Liu, Bin (Frontiers in Oncology, 2021)
Background Glioma has one of the highest mortality rates of all tumors of the nervous system and commonly used treatments almost always fail to achieve tumor control. Low-dose carbon-ion radiation can effectively target cancer and tumor cells, but the mechanisms of growth inhibition induced by heavy-ion radiation via the PI3K/Akt signaling pathway are unknown, and inhibition by heavy-ion radiation is minor in C6 cells. Methods Carbon-ion radiation was used to investigate the effects of heavy-ion radiation on C6 cells, and suppression of Akt was performed using perifosine. MTT assays were used to investigate optimal perifosine treatment concentrations. Clone formation assays were used to investigate the growth inhibition effects of carbon-ion radiation and the effects of radiation with Akt inhibition. Lactate dehydrogenase release, superoxide dismutase activity, and malondialdehyde content were assessed to investigate oxidative stress levels. Expression levels of proteins in the PI3K/Akt/p53 signaling pathway were assessed via western blotting. Results The 10% maximum inhibitory concentration of perifosine was 19.95 μM. In clone formation assays there was no significant inhibition of cell growth after treatment with heavy-ion irradiation, whereas perifosine enhanced inhibition. Heavy-ion radiation induced lactate dehydrogenase release, increased the level of malondialdehyde, and reduced superoxide dismutase activity. Akt inhibition promoted these processes. Heavy-ion radiation treatment downregulated Akt expression, and upregulated B-cell lymphoma-2 (Bcl-2) expression. p53 and Bcl-2 expression were significantly upregulated, and Bcl-2-associated X protein (Bax) expression was downregulated. The expression profiles of pAkt, Bcl-2, and Bax were reversed by perifosine treatment. Caspase 3 expression was upregulated in all radiation groups. Conclusions The growth inhibition effects of low-dose heavy-ion irradiation were not substantial in C6 cells, and Akt inhibition induced by perifosine enhanced the growth inhibition effects via proliferation inhibition, apoptosis, and oxidative stress. Akt inhibition enhanced the effects of heavy-ion radiation, and the PI3K/Akt/p53 signaling pathway may be a critical component involved in the process.